Biodisel dari Mangrove Jenis Nyamplung (Callophylum inophyllum) sebagai Alternatif Pengganti Bahan Bakar Minyak Fosil - Suyono Suyono; Ninik Umi Hartanti; Agus Wibowo; Narto Narto (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2017)
Resources of fossil fuel continue to decrease and cannot be renewed so that replacement alternative is needed. Biofuels (biodiesel) become one of the alternatives because it can be renewed and environmentally friendly. First-generation biodiesel from food sources and second generation of food waste can disrupt the availability of food. Those are inefficient because it requires extensive land for its provider. Seed of nyamplung (Callophylum inophyllum) is very potential as biodiesel raw material because of its oil content 40-70% is high compared to other types of plants, such as jatropha range of 40-60% and palm of 46-54%, raw materials saving and having twice of fuel as much as kerosene. The general purpose of this research is to produce third generation biodiesel from nyamplung  as material to overcome fossil fuel crisis especially for fishermen and farmers in coastal area of Brebes Regency and surrounding areas. To be able to achieve the goal / general target is done by assessing oil content in nyamplung seed, biodiesel synthesis, intensive culture techniques and models of development of mass culture. The biodiesel yield produced from nyamplung seed oil in this study was 82.87%, in the range of biodiesel yields of previous researchers through a single stage transesterification of 79.03-91,00%. Cetana number and alkyl ester figures in the resulting biodiesel respectively 79.5 and 99.71% have met the Indonesian National Standard (SNI). The resulting density was 893.1 kg / m3, fog point  was 20oC and total glycerol  was 0.26%, was approaching the SNI by an insignificant difference, while the acid number generated was 1.86 mg KOH/gr of biodiesel and the biodiesel viscosity was 15.7 mm2 /s has not fulfilled the SNI significantly. To improve the number of acids and viscosity is still needed refinement biodiesel synthesis process through the diversification of the number of esterification stages, alternative types and catalytic levels or optimization of transesterification reaction temperature.